Paul Cherlin, John Dewey, and the Love of Wisdom - Friedman, Robin (Eidos. A Journal for Philosophy of Culture, 2025)
Preview: /Review: Paul Benjamin Cherlin, John Dewey’s Metaphysical Theory (New York, New York, Palgrave McMillian, 2023), 170 pages./ Philosophy has traditionally been defined as the love of wisdom. Understanding the love of wisdom is crucial to Paul Cherlin’s book John Dewey’s Metaphysical Theory. Cherlin’s short but broad-ranging study offers a view of the nature and importance of philosophy, metaphysics, and of the difficult metaphysics of Dewey which Cherlin finds “deserves to be counted among the greatest metaphysical theories in the history of philosophy.”